The Impact of Pain on Patient and Physician - Longhurst, Mark F. (1984)
A patient's pain has lost its status as an expression of personal suffering and is seen by both physician and patient as a strictly physical attribute. Because of this, their communication may become oblique and subversive, effectively destroying a therapeutic relationship. The patient's failure to recover causes the physician to suffer unease and begin assuming pain-reducing postures of anger, indifference and assertiveness. The physician, to avoid this scenario, must acknowledge the existential component of the patient's pain, the reality of his own discomfort, and be open enough to give personal suffering a place in the relationship.